PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK - Dody Suryandi; Nike Hutabarat; Hartono Pamungkas (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Every child who is a victim in a crime of sexual violence or rape, at the trial stage the child victim must be a witness. The victim must repeat the story or incident that he experienced before the panel of judges, prosecutors of the defendant's lawyer and the defendant himself. The victim must not be positioned in a depressed state, both physically and psychologically. When the victim becomes a witness, the victim is treated as well as possible, in the sense that he must not be feared by outsiders both psychologically and psychologically